Black-bellied whistling duck (Dendrocygna autumnalis) brain cholinesterase characterization and diagnosis of anticholinesterase pesticide exposure in wild populations from Mexico - Rendón-Von Osten, Jaime
Rice is the main crop in the subbasin of the fluvial lagoon system of Palizada River (FLSPR) in the state of Campeche, Mexico. The pesticides used to control pests of this crop mainly are carbofuran, chlorpyrifos, and glyphosate. Black -bellied whistling duck (Dendrocgna autumnalis) is an ecologically and economically important species in the area. This duck is consumed by local inhabitants throughout the year, despite its potential exposure to pesticides. Due to its feeding habits, abundance,and nutritional value, D. autumnalis is a good indicator of environmental contamination and a potential route of human exposure to organophosphate and carbamate pesticides. In this study, the brain cholinesterase (ChE) in the frontal cerebral cortex of autochthonous ducks was characterized. In addition, the potential of the three locally used pesticides and mixtures to inhibit ChE activity was investigated and the exposure of the wild duck population during intensive pesticide applications in rice fields was evaluated. We found that acetylcholinesterase (AChE) seems to be the predominant ChE form in the biological fraction analyzed. Carbofuran was the most potent ChE inhibitor of D. autumnalis brain ChE activity from the three pesticides analyzed. Cholinesterase inhibition after exposure to pesticide mixtures predominantly was due to carbofuram. A decrease (p < 0.05) in AChE activity (>30%) was apparent in wild ducks compared to reference ducks, with recovery of ChE inhibition in wild ducks occurring months later when no pesticides were applied in the field. Dendrocygna autumnalis brain ChE is a suitable parameter for inclusion in biomonitoring programs for both environmental protection and human safety.